Call for Boycott of Pro-Israel Products in MUI Fatwa: An Analysis of Tafsīr Maqaṣidi - Annisa Fitrah; Asrizal Saiin; Anwar M. Radiamoda (UIN Sultan Syarif Kasim Riau, 2024)
This research analyzes the call to boycott Israeli products issued by the Indonesian Ulema Council (MUI) from the perspective of maqāṣidic exegesis (tafsīr maqaṣidi). The maqāṣidic approach in interpreting the Qur'an emphasizes the objectives of Sharia (maqāṣid al-sharī'ah), which include the preservation of religion (ḥifẓ al-Dīn), preservation of life (ḥifẓ al-Nafs), preservation of intellect (ḥifẓ al-'Aql), preservation of wealth (ḥifẓ al-Māl), and preservation of the state (ḥifẓ al-Daulah). The MUI's fatwa committee supports the boycott as a form of solidarity, aligning with the principles of justice and humanity in Islam, while also challenging the genocide committed by Israel against the Palestinian people. This paper is a type of library research, utilizing descriptive-analytical analysis. The findings of this research affirm that the boycott is viewed as an act of